(untitled) (Journal of Guidance and Counselling Studies, 2021)
The study examined the influence of parental career and Education on conduct Disorder among young Adults. A total of 98 participants consisting of 48 males and 50 females with age average of 13 and 20participated in the study. Their mean age was 15.30 and standard deviation age was 3.48. The participants were youth/young adults attending extra moral lesson at Nnebuisi Area Asaba and Ubulu-Uku all in Delta State, Nigeria. The instrument used for the study was developed by Uria (2000) based on parental career on conduct Disorder (PCCD). Choas (2001) found the scale to have total cronbach alpha of .64 to .71 the instrument was made up of 5 likert typed scale, with 24 items. The design of the study was a survey typed and 2 way ANOVA statistics was used in the data analysis. It was shown that significant differences existed in the manifestations of conduct disorder in both careers and educational variables. However, no interaction effect of the career and education on conduct disorder was observed. Implications and recommendations of the finding were made in the line with the results obtained.